EFEK MESON Ïƒ* PADA PERSAMAAN KEADAAN BINTANG NEUTRON - Alrizal Alrizal; A. Sulaksono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The existence of hyperon in neutron stars has been studied by relativistic mean field model. By assuming the hyperon in a neutron star will affect the equation of state and properties of neutron star. In this study, we will discuss how meson coupling constant variation affecting the equation of state of neutron stars by using relativistic mean field model and GM1 parameter which later will be compared with BSP parameter. It can be seen that by varying the coupling constants affecting the equation of state of neutron stars. Keywords : Neutron star, Hyperon, meson, Equation of state.